Deciphering the Virome of Culex vishnui Subgroup Mosquitoes, the Major Vectors of Japanese Encephalitis, in Japan - Faizah, Astri Nur; Kobayashi, Daisuke; Isawa, Haruhiko; Amoa-Bosompem, Michael; Murota, Katsunori; Higa, Yukiko; Futami, Kyoko; Shimada, Satoshi; Kim, Kyeong Soon; Itokawa, Kentaro; Watanabe, Mamoru; Tsuda, Yoshio; et al. (Viruses, 2020)
Japanese encephalitis (JE) remains a public health concern in several countries, and the Culex mosquito plays a central role in its transmission cycle. Culex mosquitoes harbor a wide range of viruses, including insect-specific viruses (ISVs), and can transmit a variety of arthropod-borne viruses (arboviruses) that cause human and animal diseases. The current trend of studies displays enhanced efforts to characterize the mosquito virome through bulk RNA sequencing due to possible arbovirus–ISV interactions; however, the extent of viral diversity in the mosquito taxon is still poorly understood, particularly in some disease vectors. In this study, arboviral screening and RNA virome analysis of Culex tritaeniorhynchus and C. pseudovishnui, which are part of the Culex vishnui subgroup mosquitoes, were performed. Results from these two mosquito species, known as the major vectors of JE virus (JEV) in Asia, collected in three prefectures in Japan were also compared with the sympatric species C. inatomii. A total of 27 viruses, including JEV, were detected from these Culex mosquitoes. Molecular and phylogenetic analyses of the detected viruses classified 15 of the 27 viruses as novel species, notably belonging to the Flaviviridae, Rhabdoviridae, Totiviridae, and Iflaviridae families. The successful isolation of JEV genotype I confirmed its continuous presence in Japan, suggesting the need for periodic surveillance. Aside from JEV, this study has also reported the diversity of the RNA virome of disease vectors and broadened the knowledge on mosquito virome profiles containing both arbovirus and ISV. Mosquito taxon seemed to contribute largely to the virome structure (e.g., virome composition, diversity, and abundance) as opposed to the geographical location of the mosquito species. This study therefore offers notable insights into the ecology and evolution of each identified virus and viral family. To the authors’ knowledge, this is the first study to characterize the viromes of the major JE vectors in Japan.